Change leadership : developing a change-adept organization - Orridge, Martin, 1947- (Gower ; Ashgate, 2009)
This concise guide explores the human aspects of change and explains how we, as leaders, can help everyone cope with change and in turn ensure our organization's long-term survival. Whether organizational change is your primary role, or whether you need to reflect on and manage the human factors of a business project for which you are responsible, Change Leadership will help you better understand the nature of change and, in doing so, develop a Change-Adept organization.